ANALISIS PENGARUH KINERJA DAN KEDISPLINAN KARYAWAN TERHADAP KUALITAS PRODUK PADA PT SIIX ELEKTRONICS INDONESIA - Raja Gukguk, Nanda; Ganda Sirait (Computer Science and Industrial Engineering, 2024)
Employees who break the rules have a negative impact on the quality of the products they produce. They may also not finish their work, be disinterested in cooperating with others, enjoy gossip, arrive late or skip work, get into arguments with coworkers, or steal company property without authorization. Defects were discovered as a result of workers' reduced focus on production quality as a result of goal pressure. This research aims to ascertain how employee discipline, performance, and both employee and performance discipline affect product quality, as well as the outcomes of using the Fishbone Diagram approach to investigate product quality. Fishbone diagrams and multiple linear regression analysis techniques are used in this quantitative study design. The study's findings indicate that there are factors that affect product quality and cause problems with performance and discipline, including man, material, method, machine, and environment factors. Additionally, there is a positive and significant relationship between employee performance and discipline on product quality at PT Siix Electronics Indonesia. These findings are in addition to the finding that there is a positive and significant relationship between employee performance and discipline on product quality at PT Siix Electronics Indonesia.